Surgical management of an isolated humeral trochlear fracture: a rare case report - Pottangadi, Rijesh; Harafan, Abdulla; Raj, Arun N.; Roshan, Shisham Hashim; Sathyan, Dhuthi Lakshmi; Kumar, Ranjith (International Journal of Research in Orthopaedics, 2025)
Isolated fractures of the humeral trochlea (Laugier’s fracture) are extremely rare, with few cases documented in literature. We report the case of a 78-year-old man with diabetes, hypertension, and chronic kidney disease who sustained a displaced intra-articular trochlear fracture following a fall. Diagnosis was confirmed with CT after plain radiographs suggested a distal humeral fracture. Open reduction and internal fixation (ORIF) were performed using a Herbert screw through an anteromedial approach. The patient achieved good functional recovery with early mobilization. This case highlights the importance of CT in diagnosis, surgical planning, and the efficacy of headless screw fixation in restoring stability and function.